Going postal : a novel of Discworld - Pratchett, Terry (Pratchett, Terry. Discworld series (New York, N.Y.), 2005)
Moist von Lipwig, alias Alfred Spangler, is given a choice of either reviving the Ankh-Morpork Post Office or death, but getting the system up and running again proves to be a near-impossible task.